The chimera of redistribution: 'Black Economic Empowerment' (BEE) in the South African fishing industry - Stefano Ponte; Lance van Sittert (Danish Institute for International Studies (DIIS), 2006)
Redistributive processes do not belong to the pantheon of Neo-liberalism. In this framework, inequality of resources can only be addressed by equality of opportunity. Even in `softer' impersonations of Neo-liberalism, corporate (mis)behaviour is tamed by corporate social responsibility, not by state disciplinary action. Yet, in the context of post-apartheid South Africa, the state can not ignore political pressure for redistribution, even if only rhetorically. The process of Black Economic Empowerment (BEE) is an attempt at marrying redistribution and Neo-liberal economic policy. The South African state, however, has different degrees of power to force real or imagined redistributive efforts in different sectors of the economy. Fisheries – along with energy, telecommunications, and mining – is one of the sectors where the allocation of licenses, exploitation rights and quotas makes the state theoretically more likely to be successful in achieving BEE. In this paper, we examine redistributive processes in the hake deep-sea trawl (HDST) industry through a historical analysis of the principles, narratives and management systems that have been used to identify certain groups as `legitimate fishers' since the late nineteenth century. We place this evolution as a background for a nuanced understanding of the first allocation of long-term fishing rights that took place in early 2006. We conclude that BEE, despite ist formal intentions, is doubly conducive to the interests of large-scale South African capital – for which investment in fishing is only one among many others. First, it has largely confirmed the historical share of fishing rights to incumbent, largely white-controlled, operators. It has also allowed for the more flexible allocation of rights via the market in response to changing environmental, economic and social conditions. Second, BEE has created a new layer of `black captains of industry' to whom incumbent players are increasingly outsourcing primary production in a volatile, high-risk, and currently loss-leading sector. While fishing operations are being outsourced under the banner of redistribution, fish trade is still effectively controlled downstream by white capital through logistics, distribution, marketing and branding assets.
Keywords: 330; Ethnische Diskriminierung; Rassenpolitik; Wirtschaftspolitik; Fischereipolitik; Fischwirtschaft; Süßwasserfisch; Strukturwandel; Wirtschaftsgeschichte; Südafrika